Collection and characterization of local cassava germplasm from the Brong - Ahafo Region - Boampong, Ebenezer (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Science degree in Plant Breeding.